2018
DOI: 10.5194/angeo-2018-65
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The asymmetric geospace as displayed during the geomagnetic storm on August 17, 2001

Abstract: Abstract.Previous studies have shown that conjugate auroral features are displaced in the two hemispheres when the interplanetary Increased tail reconnection during substorm expansion phase reduces the asymmetry.15 Copyright statement.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…The same could also be seen in Østgaard et al (), where the displacement of the centroid is reduced during expansion phase in the presented events. More recently, Østgaard et al () studied the longitudinal displacement of the conjugate aurora during a geomagnetic storm. Two substorms occurred in the time interval considered, and Østgaard et al () found that the relative displacement between the hemispheres was smallest after each substorm, and build up in the interval between the substorms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same could also be seen in Østgaard et al (), where the displacement of the centroid is reduced during expansion phase in the presented events. More recently, Østgaard et al () studied the longitudinal displacement of the conjugate aurora during a geomagnetic storm. Two substorms occurred in the time interval considered, and Østgaard et al () found that the relative displacement between the hemispheres was smallest after each substorm, and build up in the interval between the substorms.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Østgaard et al () studied the longitudinal displacement of the conjugate aurora during a geomagnetic storm. Two substorms occurred in the time interval considered, and Østgaard et al () found that the relative displacement between the hemispheres was smallest after each substorm, and build up in the interval between the substorms. Statistical support of the reduction is seen in Milan et al (), who did a superposed epoch analysis of substorms using auroral images from the northern hemisphere obtained by IMAGE.…”
Section: Discussionmentioning
confidence: 99%
“…In an event study, Østgaard, Humberset, et al () showed that the longitudinal displacement of conjugate auroral features were reduced during the expansion phase in two subsequent substorms. In a more recent study, Østgaard et al () found that the asymmetry of conjugate auroral features reached a minimum after substorms occurring during a geomagnetic storm. Ohma et al () presented a multicase study of conjugate images from substorms, showing a reduced displacement in several events and an apparent relation between the reduction of asymmetry and increase in tail reconnection rate.…”
Section: Introductionmentioning
confidence: 96%
“…Earlier studies have found strong evidence that lobe reconnection is more efficient in the hemisphere inclined toward the Sun, that is, the local summer hemisphere (Crooker & Rich, ; Frey et al, ; Koustov et al, ; Østgaard et al, ; Wilder et al, ; Yakymenko et al, ), from observing the sunward ionospheric convection velocity in the dayside polar cap during northward IMF. However, most studies have focused on the dependence on the solar wind electric field, E sw = v sw B T , where B T is the transverse component of the IMF, BT=By2+Bz2 (Koustov et al, ; Sundberg et al, ; Wilder et al, ; ; Yakymenko et al, ), likely to be the most important controlling factor on the lobe reconnection rate during purely northward IMF.…”
Section: Introductionmentioning
confidence: 99%